PENGARUH BEBAN KERJA DAN KELELAHAN KERJA TERHADAP KINERJA PEGAWAI PADA PUSKESMAS NGROTO - KURNIAWAN, ARIEF (Al Iqtishadiyah: Journal of Islamic Economics and Finance, 2024)
Everyone's workload is different depending on the type of work. Workloads that are disproportionate to workers' ability for longer can cause work fatigue. As a result, it can affect performance. This study aimed to determine the relationship between workload and work fatigue on employee performance at the Ngroto Public Health Center, Blora City, in 2024. This study was an Analytical Survey research with a Cross-Sectional approach. The sampling technique used was Total Sampling, the entire population of 53 employees minus five employees who had been interviewed during the preliminary study. The results of statistical tests using the Chi-Square test showed that there was a relationship between workload and employee performance at the Ngroto Public Health Center, Blora City, with a value (p-value = 0.005) (?< 0.05). It is hoped that the Puskesmas need to pay more attention to the aspects of the workload on employees to show optimal results.